Pemberdayaan Digital Desa Wisata Melalui Integrasi AI Avatar dan Sistem Pemasaran Berkelanjutan - Mohammad Wartaka; Sumardjono Sumardjono; Arif Harbani; Dadi Muhamad Hasan Basri; Ashya Nur Azrina; Fanissa Wafha Nurhilma (Jurnal Penelitian dan Pengabdian Masyarakat, 2026)
This community service program aimed to strengthen the digital capacity of the Purwabakti Tourism Awareness Group (Pokdarwis) through the integration of Artificial Intelligence (AI) Avatar technology, social media management optimization, and the development of a digital tourism website. The program applied a Participatory Action Research (PAR) approach consisting of five stages: socialization and Focus Group Discussion (FGD), digital content creation training, technology implementation, continuous mentoring, and program evaluation. The activity involved 20 Pokdarwis members using a learning approach consisting of 30% theoretical explanation and 70% practical activities. The results demonstrated improved partner capabilities in managing digital tourism promotion, indicated by an 894% increase in Instagram reach, 40.6 thousand content views, 941 interactions, and a 575% increase in tourist visits. Furthermore, the program successfully developed an integrated tourism information platform and established an independent digital management team. These findings indicate that the combination of appropriate technology adoption and continuous mentoring can strengthen community capacity and support sustainable digital transformation in rural tourism development.